Ecological preferences and abundances of populations of protected lichens in linden forests on the Salair Ridge in Altai Territory - Evgeny A. Davydov; Natalia V. Elesova; Irina A. Khrustaleva; Yulia V. Storozhenko; Lidia S. Yakovchenko (Acta Biologica Sibirica, 2022)
For a comprehensive assessment of the habitats of rare and vulnerable lichen species, the Tilia sibirica forest in the Zarinsky Districts of the Altai Territory was studied. Plant communities were described on 25 sample plots. Seven species of lichens listed in the Red data book of the Altai Territory were found in the studied forests: Graphis scripta, Heterodermia speciosa, Lobaria pulmonaria, Nephroma bellum, Ramalina roesleri, R. sinensis, and R. vogulica. New quantitative data on cenopopulations of the studied lichen species in Salair region have been obtained. Ecological preferences are indicated for each species and the abundance of populations (dm2/ha) are calculated. Linden forest is shown to have a high conservation value regarding lichens.